Cytogenetic study of five species of medicinal plants from Maha Sarakham Province, Thailand - PIYAPORN SAENSOUK; NATKAMON SAEN-IN; SURAPON SAENSOUK (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Saensouk S, Saen-in N, Saensouk P. 2022. Cytogenetic study of five species of medicinal plants from Maha Sarakham Province, Thailand. Biodiversitas 23: 3593-3603. The cytogenetic study of five species of medicinal plants, namely Butomopsis latifolia (D. Don) Kunth, Iris domestica (L.) Goldblatt & Mabb., Limnocharis flava (L.) Buchenau, Murdannia loriformis (Hassk.) R.S. Rao & Kammathy, and Pontederia hastata L. from Maha Sarakham Province, northeastern Thailand was conducted. This study aimed to investigate the chromosome numbers, fundamental number (NF), karyotype forms, and perform ideogram analysis of the five species. The cytogenetic characteristics, including the chromosome number, karyology (fundamental number (NF), karyotype formula), symmetrical karyotype, chromosome size, relative length (RL), centromeric indexes (CI), and ideograms of B. latifolia (D. Don) Kunthwere studied for the first time. The chromosome numbers of five medicinal plant species were reported as 2n = 14 (B. latifolia (D. Don) Kunth)- 80 (I. domestica (L.) Goldblatt & Mabb.). Moreover, the NF had 28 (B. latifolia (D. Don) Kunth) - 80 (Iris domestica). Two species (M. loriformis(Hassk.) R.S. Rao & Kammathyand P. hastata L.) were recognized as having symmetrical karyotypes. Three species, namely B. latifolia (D. Don) Kunth, Iris domestica, and L. flava(L.) Buchenau were reported as having asymmetrical karyotypes. Chromosomes of large size (L), chromosomes of medium size (M), and chromosomes of small size (S) were observed. Ideograms of five species were provided in this study. The NF, RL, CI, chromosome size, and ideograms of all species were reported for the first time in this study. The karyotype formulae of the five species, except the karyotype formula of P. hastata L., differed from those previously studied. The cytogenetic data of the five species in this study can be used for identification.